1993
DOI: 10.1016/0014-5793(93)81667-o
|View full text |Cite
|
Sign up to set email alerts
|

A comment on the absence of calcium regulation of human thioredoxin reductase

Abstract: It has been previously suggested that human thioredoxin reductase activity is regulated by calcium. However, the activity of a purified form of human placental thioredoxin reductase was found to not be affected by mM concentrations of calcium, well above intra-and extracellular physiological levels. Furthermore, the suggestion that an E~F hand is present in Escherichia coli thioredoxin reductase is strongly contested. These current results suggest that human thioredoxin reductase is not regulated by calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…In addition, a previous study suggested that Ca 2ϩ might be a potential inhibitor of mammalian TR (25)(26)(27), although another study found no inhibitory effects of calcium on TR1 activity (28). The possibility remained that the differences observed were due to analyses of different TR isozymes.…”
Section: Identification and Subcellularmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, a previous study suggested that Ca 2ϩ might be a potential inhibitor of mammalian TR (25)(26)(27), although another study found no inhibitory effects of calcium on TR1 activity (28). The possibility remained that the differences observed were due to analyses of different TR isozymes.…”
Section: Identification and Subcellularmentioning
confidence: 77%
“…However, which TR isozyme is the most abundant in skin cells and was inhibited in these studies is not known. Subsequently, TR1 was reported to be insensitive to calcium inhibition (28,35). However, the most recent study found that TR1, but not TR3, is inhibited by Ca 2ϩ (36).…”
Section: Discussionmentioning
confidence: 99%
“…80 226.01 f 18.54 63. 82 6723 7414 6304 8009 2009 3102 9507 2311 4818 6226 4329 6323 8302 9126 5009 3313 7107 9123 5122 7806 3807 6716 9048 5209 7409 8402 4010 6111 81 13 8219 4211 3106 1118 8315 9202 3808 5012 3408 6709 3308 2120 9702 8120 41 17 302 8012 8135 3109 6308 9106 8107 8118 3817 6024 2003 8105 3301 7224 5703 21 17 6717 8412 3309 3103 2209 61 I1 27 1116 3310 3104 2503 2206 2007 3403 3410 6503 102 1002 5202 2204 2009 1506 4305 3507 3405 4309 3107 4502 2505 5205 1107 2108 1207 3005 507 4205 2304 6208…”
Section: Not Detectedunclassified
“…The cytosolic isoform of TGR shows a noticeably higher sensitivity to calcium ion inhibition in comparison to the corresponding mitochondrial isoform [10]. Taking into account the strict similarity between calcium and lanthanum ions, we have studied the effects of LaCl 3 on TrxR, in order to make a comparison with the results previously obtained on TrxR treated with calcium ions, especially considering the differential and contrasting inhibitory effects observed with this cation [1][2][3][4][5][6][7][8]. Lanthanum has an ionic radius similar to that of calcium and exhibits comparable coordination chemistry [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the effect of calcium on TrxR still is an open problem as some reports indicate that TrxR is inhibited by calcium ions [1][2][3][4][5], while other studies show no effect of calcium ions even at relatively high concentrations [6][7][8]. This ambiguity probably depends on the different enzyme preparations under study (e.g.…”
Section: Introductionmentioning
confidence: 99%